Weight changes and estrous cycles after abortion in beef heifers - Wright, J.M.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety-one pregnant, crossbred Angus heifers aborted after receiving an injection of a prostaglandin analog at an average of 50, 75, 100, or 122 days of gestation. Weight change in the first 3 weeks after abortion and subsequent estrous cycles were observed. No detrimental effects were noted in those heifers aborting at 50 or 75 days of gestation, and growth rate was not altered. Those heifers aborting at 100 days of gestation exhibited a decreased growth rate; those aborted at 122 days lost weight. There was more udder development, vaginal discharge, and retained membranes in heifers aborted later in gestation. Typically, heifers exhibited estrus within 5 days after abortion, then had 8- to 12-day cycles until a normal cycle occurred. Heifers aborted at 50 days of gestation required an average of 7.5 days prior to the estrus of their first normal cycle, 13.2 days if aborted at 75 days, 16.7 days if aborted at 100 days, and 24.7 days if aborted at 122 days.
Keywords: Beef; Estrous; Abortion; Heifers